Pembentukan Karakter Cinta Budaya Melalui Pembelajaran Seni Tari dan Tradisi Menyanyikan Lagu Daerah di Sekolah Dasar - Miskiyyah, Sylvia Zakiyyatul; Puspita, Putri Indah; Maulidia, Alfiana Rahma; Yulia, Nurul Mahruzah (CV. Kurnia Grup, 2025)
The purpose of this study was to investigate the formation of a love of culture in elementary school students taught traditional dance and song singing. This research is based on the fact that internalizing local cultural values ​​from an early age is an important part of sustainable character education. Primary data were obtained through in-depth interviews and observations, as well as secondary data from literature related to character education and culture. The study used a descriptive qualitative approach with a case study approach, and data analysis was carried out through descriptive reduction, presentation, and drawing conclusions. To ensure the validity of the findings, triangulation of sources and techniques was used. The results showed that the mechanisms of habituation, direct experience, and teacher role models formed a love of culture character through regular learning of traditional dance and song singing. Students demonstrated better cultural knowledge, pride in local culture, social skills, discipline, and self-confidence. By combining these two activities, the school environment became more conducive to cultural preservation and character education. These results are consistent with the theory of arts and culture learning (Efland, 2002) and Lickona's (1991) theory of character education. In short, learning the art of dance and singing regional songs is not only a cultural activity, it can also be used as a contextual, sustainable, and successful character teaching strategy to foster students' love of culture.